Model Sistem Rujukan Gelandangan dan Pengemis di Camp Assesment Dinas Sosial DIY - Jahidin, Asep; -, Sarif (Social Welfare Study Program, 2017)
This article disucesses referral system model of beggars and homeless treatment as part of social problems solution in Yogyakarta. The government of Yogyakarta has published the Special Regulation of Yogyakarta, among others Regulation No. 16 of 1956, (16/1956) and Provincial Regulation No. 1 year 2014 on Handling Homeless and Beggars. The goal is doing outreach to prevent homeless and beggars in cooperation with the police, Provincial Satpol PP and Dinsosnakertrans in Yogyakarta province are Kota, Sleman, Bantul, Gunung Kidul, and Kulonprogo utilizing Social Service Assessment Camp for identification and assessment. Camp Assessment is a temporary shelter for homeless and beggars (Gepeng). The finding shows that in the Assesment Camp, these groups have access to social services in the form of basic needs, medical health and coaching/guidance. In addition, social services guidance or coaching provided by the Assesment Camp for the sprawl is in the form of guidance of motivation, sports, religion, art, Mental Social and Citizenship. Upon obtaining social services, clients are involved in Case Conference meetings to determine whether a client can be repatriated or referred to social welfare institutions in accordance with the client’s source system. The research utilises a qualitative approach by field research and literature review. This article suggests for instensification of supervision and monitoring on the program to ensure sustainability aspect. Keywords: assessment, homeless, beggars, social services assessment camp, referral system model.